Hungarian Monitoring, 31 May 1989 . [Magyar rádiófigyelő], 1989. május 31 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Reports on sitting of Soviet parliament - Rude Pravo article on Gabčíkovo-Nagymaros and environmental protection - President Bush statement in FRG on transformation of Eastern Europe Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) Central Committee's announcement on Imre Nagy - Personal documents belonging to unlawfully sentenced and executed Imre Nagy handed over to his daughter - Secretary of state Borics continues talks on details of Imre Nagy's funeral - Reactions to Károly Grósz's TV statement on Imre Nagy - From September, other languages alongside Russian can be taught in primary schools - Európa Press publishes memoirs of Ferenc Nagy and Miklós Horthy Economy: - Hungary and IMF sign USD 110 million loan agreement Külpolitika: - Tudósítások a szovjet parlament üléséről - Rude Pravo cikk Bős-Nagymarosról és a környezetvédelemről - Bush elnök Magyarországról és a kelet-európai átalakulásról is nyilatkozott az NSZK-ban Belpolitika: - Az MSZMP KB közleménye Nagy Imréről - Átadták Nagy Imre lányának a törvénytelenül elit élt és kivégzett miniszterelnök személyes dokumentumait - Borics államtitkár megbeszéléseket folytatott a Nagy Imre-temetés részleteiről - Grósz Károly Nagy Imréről való TV-nyilatkozatának visszhangja - Szeptembertől az ált. iskolákban megindulhat az orosz helyett más idegen nyelv oktatása - Az Európa Kiadó megjelenteti Nagy Ferenc és Horthy Miklós emlékiratait Gazdaság: - Magyarország és a Világbank 110 millió dolláros kölcsönről írt alá megállapodást